Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/00207454.2011.642039
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Calcification Inhibitors in Patients With Intracerebral Hemorrhage

Abstract: The vascular calcification regulators and inflammatory markers including fetuin-A, osteopontin (OPN), and matrix Gla protein (MGP) may play an important role in the development of intracerebral hemorrhages (ICHs). So far, the relationship between these parameters and ICH has not been studied. Therefore, this study was designed to elucidate whether fetuin-A, MGP, and OPN are involved in the pathophysiology of ICH. The ICH group consisted of 27 consecutive patients with spontaneous ICH evaluated in the neurology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Fetuin-A levels were significantly decreased in patients with ICH in comparison to the controls. Decreased fetuin-A levels in the patients who had an ICH support the hypothesis that inflammatory processes and/or vascular calcifications play a role in the pathogenesis of this condition [12]. In Alzheimer disease (AD), Geroldi et al showed that fetuin-A concentrations in CSF of AD patients were consistently lower than the levels in the CSF taken from non-demented controls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fetuin-A levels were significantly decreased in patients with ICH in comparison to the controls. Decreased fetuin-A levels in the patients who had an ICH support the hypothesis that inflammatory processes and/or vascular calcifications play a role in the pathogenesis of this condition [12]. In Alzheimer disease (AD), Geroldi et al showed that fetuin-A concentrations in CSF of AD patients were consistently lower than the levels in the CSF taken from non-demented controls.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, fetuin-A also acts as a negative acute-phase protein and enhance phagocytosis of apoptotic cells by monocyte-derived macrophages [11]. Furthermore, there are various studies conducted on patients with neurodegenerative diseases, multiple sclerosis, intracerebral hemorrhage and ischemic stroke showing association of fetuin-A with central nervous system pathologies [12][13][14][15]. There is no report in the literature investigating the possible connection between fetuin-A levels and CP calcification.…”
Section: Introductionmentioning
confidence: 96%
“…Acar і співавт. [4] встановили, що у хворих з геморагічним інсультом концентрація MGP у сироватці крові набагато менша, ніж у контрольній групі. Крім того, цей показник у хворих, що померли внаслідок крововиливу у мозок, був достовірно нижчим, ніж у тих, хто вижив.…”
Section: результати та їх обговоренняunclassified
“…However, the role of ALP on clinical outcomes of ICH patients has not been fully interpreted in previous studies conducted in a single center with relatively small cohort, and the underlying mechanism remains unclear. Some suggested that vascular dysfunction and atherosclerotic process may play a crucial role in ICH clinical outcomes ( 16 , 18 ).…”
Section: Introductionmentioning
confidence: 99%